2017
DOI: 10.1590/1980-5373-mr-2016-0927
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic Performance of Mallow and Jute Natural Fabrics Reinforced Epoxy Composites in Multilayered Armor

Abstract: Natural fiber reinforced polymer composites have recently been investigated as a component of multilayered armor system (MAS). These composites were found to present advantages when replacing conventional high strength synthetic aramid fabric laminate composite (Kevlar TM , with same thickness, as MAS second layer. Continuous and loose natural fibers were up to now mostly used to reinforce these ballistic composites. Only two natural fabrics reinforced polymer composite were so far used with same purpose. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 29 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…The study on the effect of natural fibers hybrid composites has been reported by Nascimento et al [ 148 ] using mallow and jute natural fabrics reinforced epoxy for multi-layered armor. Through the study done, 100% mallow fabric, 70/30 and 50/50 of mallow fabric and jute fabric, respectively can be considered as suitable material for use in ballistic shield as all these materials meet the requirement of standard NIJ 0101.06 as shown Figure 22 .…”
Section: Hybrid Natural Fiber Reinforced Polymer Composites For Bumentioning
confidence: 99%
“…The study on the effect of natural fibers hybrid composites has been reported by Nascimento et al [ 148 ] using mallow and jute natural fabrics reinforced epoxy for multi-layered armor. Through the study done, 100% mallow fabric, 70/30 and 50/50 of mallow fabric and jute fabric, respectively can be considered as suitable material for use in ballistic shield as all these materials meet the requirement of standard NIJ 0101.06 as shown Figure 22 .…”
Section: Hybrid Natural Fiber Reinforced Polymer Composites For Bumentioning
confidence: 99%
“…In the production of epoxy matrix composites reinforced with natural fibers [10,11,12,13,14], after mixing the polymer and the fibers in the desired ratio, the conventional curing time used is 24 hours [15,16,17,18,19,20,21,22,23,24]. However, this time may be significantly different from that required for the complete curing reaction of the polymer matrix and therefore of the composite to be manufactured.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, the differential scanning calorimetry (DSC) analysis was performed to evaluate if the total curing time of the epoxy resin could be less than the previously reported time of 24 h [15,16,17,18,19,20,21,22,23,24]. This would optimize the availability of equipment such as presses and metal molds, as well as reduce the total production costs.…”
Section: Introductionmentioning
confidence: 99%
“…
Figure 20.(a) Schematic of a complete MAS, (b) indentation depth measurement with laser sensor caliper, (c) schematic view of the ballistic experimental setup. 93 MAS: multilayered armor systems.
…”
Section: Natural Fibers-based Pmcsmentioning
confidence: 99%
“…Actually, this tendency is not new, it was adapted since the discovery of Basalt in 1923 which was then classified as a material of choice for military research and was extensively used during the Second World War. 89 Very recently, the use of less expensive, abundant, renewable, degradable, recyclable, and regarded as environmentally friendly Sisal fibers, 87 Curaua, 90 Giant Bamboo, 91 Malva, 92 Mallow, 93 Jute, [92][93][94] bagasse, 95 Rami, 96 and Coir 97 fibers attracted the Brazilian Monteiro's group who investigated the ballistic efficiency of epoxy composites reinforced with these different fibers in MAS.…”
Section: Natural Fibers-based Pmcsmentioning
confidence: 99%